Hematological Profile in Schistosoma mansoni Infected Mice Treated with Commiphora molmol Extract Compared with Praziquantel - Alkazzaz, Mohammad Aziz; Adel Aziz, Amer Ragheb; Elmahalawy, Ehab K; Hassan, Amal A (PSM Biological Research, 2018)
As Schistosoma mansoni worms inhabit the portal triad of infected hosts, deleterious changes were encountered in the blood picture. The aim of the study is to explore the damaging hematological effects due to S.mansoni infection in albino mice before and after treatment with either Commiphora molmol extract or Praziquantel. Seventy two albino mice were recruited in this study and divided into 4 groups of 18 mice each, 54 of them were infected with S.mansoni cercariae.7 weeks post-infection, infected animals were treated with 500 mg/kg either as a single dose for 2 days in Praziquantel or for 5 consecutive days in Commiphora molmol extract. Blood samples were collected at 1, 2 and 4 weeks after treatment for assessment of complete blood counts (Hb, erythrocytes count, haematocrite value, MCV, MCH, MCHC, Platelet count, leucocytic count and differential leucocytic counts).S.mansoni infection resulted in multiple damaging effects of the blood profile on infected non-treated hosts as evidenced by decrease in red blood cells and platelets and rise in white cells with the advance of infection. Treatment with Praziquantel corrected the blood profile of erythrogram and the platelet count in progressive manner with advance of time after treatment more than Commiphora molmol Extract. This study declared that Praziquantel and Commiphora molmol extract were safe drugs without dverse hematological effects on infected treated mice with more ameliorative action achieved by Praziquantel than Commiphora molmol extract.